Preparing Teachers of English Language Learners: Empirical Evidence and Policy Implications - López, Francesca; Scanlan, Martin; Gundrum, Becky (Education Policy Analysis Archives, 2013)
In this study, we examined the degree to which the requirements in each state’s teacher education programs reflect current theory and practice for teachers of ELLs in their coursework, and how these requirements in turn are related to 4th grade Hispanic ELL’s reading outcomes on the National Assessment of Educational Progress. We found that required coursework on English language development and assessment were positively related to Hispanic ELLs' reading outcomes. Moreover, states that require both specialist certification, and all teachers to have some level of training to meet the needs of ELLs, also tend to have higher levels of achievement than states that do not have these requirements.